Nanobased intravenous and transdermal drug delivery systems - Gundloori, Rathna V. N.; Singam, Amarnath; Killi, Naresh (Applications of Targeted Nano Drugs and Delivery Systems, 2019)
In this chapter we bring in the collective information about intravenous and transdermal nano drug delivery systems (DDSs), which include different kinds of constituents used for the design of nano DDSs, their various forms, methods, and characterization of nanoformulations.